2007
DOI: 10.2307/4125320
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Causes of Rensch's Rule: Does Sexual Size Dimorphism in Arthropods Result from Sex Differences in Development Time?

Abstract: A prominent interspecific pattern of sexual size dimorphism (SSD) is Rensch's rule, according to which male body size is more variable or evolutionarily divergent than female body size. Assuming equal growth rates of males and females, SSD would be entirely mediated, and Rensch's rule proximately caused, by sexual differences in development times, or sexual bimaturism (SBM), with the larger sex developing for a proportionately longer time. Only a subset of the seven arthropod groups investigated in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
164
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(174 citation statements)
references
References 18 publications
6
164
1
3
Order By: Relevance
“…Genetic variation in SSD generated by genomic deficiencies violated Rensch's rule, such that the within-species allometric pattern is opposite to the among-species pattern in Drosophila (Huey et al, 2006;Blanckenhorn et al, 2007b). Although sex differences in development time are principally expected to produce corresponding sex differences in body size (Blanckenhorn et al, 2007a;Teder, 2013), the SSD and SDtD allometry patterns found here (Figure 2) do not agree qualitatively, thus failing to provide explanatory power regarding their relationship. The lack of a direct connection may be mediated by the negative genetic correlation between wing size and development time we found (Figure 3), which was clearly determined by the induced genetic effects ( Figure 5).…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…Genetic variation in SSD generated by genomic deficiencies violated Rensch's rule, such that the within-species allometric pattern is opposite to the among-species pattern in Drosophila (Huey et al, 2006;Blanckenhorn et al, 2007b). Although sex differences in development time are principally expected to produce corresponding sex differences in body size (Blanckenhorn et al, 2007a;Teder, 2013), the SSD and SDtD allometry patterns found here (Figure 2) do not agree qualitatively, thus failing to provide explanatory power regarding their relationship. The lack of a direct connection may be mediated by the negative genetic correlation between wing size and development time we found (Figure 3), which was clearly determined by the induced genetic effects ( Figure 5).…”
Section: Discussionmentioning
confidence: 38%
“…Our study also revealed the expected genetic correlation between male and female developmental times (Figure 2b), but the slope of this regression did not significantly differ from unity. The hypoallometric pattern for SSD and isometric pattern for SDtD are thus qualitatively inconsistent, and therefore the sex differences, as well as the SSD allometry not following Rensch's rule displayed in Figure 2, are only distinct for wing size (and not developmental time), which is also true across Drosophila species (Blanckenhorn et al, 2007a). Overall, therefore, sex differences in developmental time cannot explain sex differences in body size, and SDtD cannot explain the allometric pattern of SSD in any simple way, confirming similar conclusions of previous studies (Blanckenhorn et al, 2007a;Testa et al, 2013).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These variations in developmental and growth rates are also considered responsible for the variation in sizes including that of the male being smaller than the female in ectothermic organisms (e.g. Teder and Tamaru, 2005;Blanckenhorn et al, 2007;Esperk et al, 2007;Stillwell et al, 2007Stillwell et al, , 2010. Fecundity selection is believed to be the driving force in the occurrence of female biased sexual size dimorphism in most of the insect orders (Hönek, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…SSD in forest millipedes has successfully been understood as volumetric measurements using Centrobolus to corrobrate Rensch's rule [4][5][6][7] . Based on the assumption of equal developmental rates in males and females, the proximate cause for Rensch's rule is sexual bimaturism [10][11] . The general trend of SSD has been calculated for Centrobolus and sexual bimaturism shown [7,11] .…”
Section: Introductionmentioning
confidence: 99%